2021
DOI: 10.1136/bmjqs-2021-013150
|View full text |Cite
|
Sign up to set email alerts
|

Days alive and at home after hip fracture: a cross-sectional validation of a patient-centred outcome measure using routinely collected data

Abstract: BackgroundDays alive and at home (DAH) is a patient centered outcome measureable in routinely collected health data. The validity and minimally important difference (MID) in hip fracture have not been evaluated.ObjectiveWe assessed construct and predictive validity and estimated a MID for the patient-centred outcome of DAH after hip fracture admission.MethodsThis is a cross-sectional observational study using linked health administrative data in Ontario, Canada. DAH was calculated as the number of days alive w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 60 publications
0
12
1
Order By: Relevance
“…Few studies have assessed prevalence and outcomes of delirium in patients admitted directly from home, who likely have lower levels of frailty, dementia, and comorbidities associated both with delirium and adverse outcomes, and in whom days at home following admission with a hip fracture has been demonstrated to be a valid and important patient-centred outcome. 21,31 The reported prevalence of delirium (14.1%) in this study is slightly lower than reported by Krogseth et al 8 (19%). This may reflect the much smaller, selected sample with high levels of missing data in the latter study (85/207 did not have a preoperative delirium assessment), and different assessment methods (4AT embedded in routine practice, versus Confusion Assessment Method-based specialist assessment).…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Few studies have assessed prevalence and outcomes of delirium in patients admitted directly from home, who likely have lower levels of frailty, dementia, and comorbidities associated both with delirium and adverse outcomes, and in whom days at home following admission with a hip fracture has been demonstrated to be a valid and important patient-centred outcome. 21,31 The reported prevalence of delirium (14.1%) in this study is slightly lower than reported by Krogseth et al 8 (19%). This may reflect the much smaller, selected sample with high levels of missing data in the latter study (85/207 did not have a preoperative delirium assessment), and different assessment methods (4AT embedded in routine practice, versus Confusion Assessment Method-based specialist assessment).…”
Section: Discussioncontrasting
confidence: 68%
“…Returning to live at home on discharge is important, with days alive and at home following a hip fracture validated as a patient-centred outcome for patients aged > 50 years. 21 In a study of 207 patients admitted directly from private homes, Krogseth et al 8 reported an inpatient delirium incidence of 39%, and associations with higher mortality and risk of new institutionalization. Determining whether similar associations exist in large, population-representative datasets with routine delirium assessment is important for clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Our primary outcome is place of care/residence at 6 and 12 months postsurgery (eg, death, acute hospital, long-term care, rehabilitation, home with support, home no support). 19 Our secondary outcomes are return to the emergency department within 90 days of hospital discharge (and reason), hospital readmissions with 90 days of discharge (and reason), new long-term care admission, an adjusted validated day alive at home indicator, 20 survival at 6 and 12 months, health service utilisation (eg, follow-up visits with family physicians or specialists, new or increased home care services) and healthcare costs across the system using a costing macro developed at ICES. 21 For patients discharged home with home care, complex continuing care or long-term care, we will additionally capture functional status at rehabilitation discharge (eg, self-care, sphincter control, transfers, locomotion, communication, social cognition), cognition level and health-related quality of life.…”
Section: Methodsmentioning
confidence: 99%
“…Several terms have been applied to the construct captured by DAH in the literature including but not limited to DAH, time at home, days spent at home, days alive and out of hospital, days alive and at home, home time and healthy DAH 11–13 16 18–20. Accordingly, definitions have been inconsistent.…”
Section: Introductionmentioning
confidence: 99%